2001
DOI: 10.1093/nar/29.11.e54
|View full text |Cite
|
Sign up to set email alerts
|

Specific detection of DNA and RNA targets using a novel isothermal nucleic acid amplification assay based on the formation of a three-way junction structure

Abstract: The formation of DNA three-way junction (3WJ) structures has been utilised to develop a novel isothermal nucleic acid amplification assay (SMART) for the detection of specific DNA or RNA targets. The assay consists of two oligonucleotide probes that hybridise to a specific target sequence and, only then, to each other forming a 3WJ structure. One probe (template for the RNA signal) contains a non-functional single-stranded T7 RNA polymerase promoter sequence. This promoter sequence is made double-stranded (hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…The CytAMP assay is based on isothermal signalmediated amplification of RNA technology (SMART) (12,24). Two targetspecific single-stranded oligonucleotide probes (the "template" probe and the "extension" probe) are designed so that they can anneal to each other only in the presence of the target, thus forming a structure called a three-way junction (3WJ) (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The CytAMP assay is based on isothermal signalmediated amplification of RNA technology (SMART) (12,24). Two targetspecific single-stranded oligonucleotide probes (the "template" probe and the "extension" probe) are designed so that they can anneal to each other only in the presence of the target, thus forming a structure called a three-way junction (3WJ) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Following 3WJ formation, DNA polymerase extends the short extension probe so that a single-stranded promoter sequence on the template probe is converted into a functional double-stranded promoter for RNA polymerase, which in turn allows generation of multiple copies of an RNA signal. The RNA signal generated is further increased by additional rounds of extension and transcription (12,24). Thus, the SMART process is based on signal rather than target amplification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These assays rely on the fact that only the doublestranded promoter is fully functional, and allows T7 RNA polymerase to generate multiple copies of RNA molecules (Chan and Fox, 1999). Wharam et al (2001) have reported a dual enzyme technology, termed signal mediated amplification of RNA technology (SMART), which is based on the formation of a three-way junction (3WJ) structure (Fig. 8).…”
Section: Transcription-based Amplificationmentioning
confidence: 99%